2012
DOI: 10.1177/1090198112447800
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Intrapersonal Predictors of Adolescent Risky Sexual Behavior and Outcomes

Abstract: The present study was designed to test a model of contextual and intrapersonal predictors of adolescent risky sexual behaviors and of sexually transmitted infection diagnoses. Using Waves I and II from the National Longitudinal Study of Adolescent Health, the authors estimated a structural model in which intrapersonal factors such as adolescents' attitudes about sex, perceived parental norms, knowledge about sexual health, and birth-control self-efficacy partially mediated the effects of contextual factors suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
1
23
0
1
Order By: Relevance
“…While past studies have identified how adolescent reproductive KAB affects initiation of sexual intercourse, contraceptive use, and pregnancy during adolescence, [58, 10, 20, 23, 24] these studies were unable to address how these KAB formed during adolescence impact pregnancy outcomes later in life for men. As many of these prior studies focus exclusively on women, [57] it is particularly important to investigate this relationship for men in order to better understand the paths leading to various fatherhood states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While past studies have identified how adolescent reproductive KAB affects initiation of sexual intercourse, contraceptive use, and pregnancy during adolescence, [58, 10, 20, 23, 24] these studies were unable to address how these KAB formed during adolescence impact pregnancy outcomes later in life for men. As many of these prior studies focus exclusively on women, [57] it is particularly important to investigate this relationship for men in order to better understand the paths leading to various fatherhood states.…”
Section: Discussionmentioning
confidence: 99%
“…[6, 24] Participants were presented with the statements “Getting someone pregnant at this time in your life is one of the worst things that could happen to you” and “It wouldn’t be all that bad if you got someone pregnant at this time in your life.” Higher scores indicate a more positive attitude towards getting someone pregnant.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a resiliency paradigm orients researchers and practitioner to positive factors in youth’s lives that become the focus of change strategies designed to enhance strengths. Some of the studies in this theme issue focus on adolescent strengths, but do not necessarily apply a resiliency paradigm (e.g., Shneyderman & Schwartz, 2013). …”
mentioning
confidence: 99%
“…No entanto, os resultados têm sido inconsistentes no que respeita a saber-se que conjunto de preditores é mais influente para cada indicador ou resultado de comportamento sexual de risco. Na medida em que os diferentes indicadores são importantes para os diferentes comportamentos, há que centrar as intervenções em processos múltiplos, de forma a conseguir-se o máximo impacto (Shneyderman & Schwartz, 2012). De forma a conseguir-se o máximo impacto como foi constatado num estudo de Cunha--Oliveira (2013), aqueles que não aderem aos programas de intervenção são aqueles que mais deles necessitariam.…”
Section: Enquadramentounclassified